Pembangunan ekonomi berkelanjutan: Penerapan fintech terhadap inklusi keuangan pada era ekonomi digital - Arliyanti, Shilla Putri; Astuti, Ratna Fitri (Journal of Economics Research and Policy Studies, 2024)
The existence of fintech strongly supports the increase in financial inclusion; when financial inclusion increases, it will encourage the realization of sustainable development. This study aims to determine how the effect of the application of fintech using mobile banking, internet banking and ATM variables on financial inclusion in the digital economy era. Data analysis used multiple regression analysis with the OLS (Ordinary Least Square) method using secondary data collection techniques sourced from Bank Indonesia and the Deposit Insurance Corporation collected from 2015 - 2023. The results of this study indicate that mobile banking has a significant positive effect on financial inclusion. Internet Banking variable has no significant effect on financial inclusion. ATM Card variable has no significant effect on financial inclusion.